125I-labeled peptide mapping of some heat-modifiable proteins of the gonococcal outer membrane. - Swanson, J (1980)
Gonococci from opaque colonies have cell wall outer membrane proteins that are lacking from organisms which form transparent colonies. These "colony opacity-associated" proteins are among a group of "minor" proteins that exhibit heat modification of their apparent subunit molecular sizes, are easily extracted by deoxycholate, have apparent subunit molecular weights varying from 24,000 to 29,000 and are exposed on the surfaces of gonococci. Other minor proteins found on gonococci are the "leukocyte association proteins," whose presence correlates with reactivities of gonococci with human neutrophils. Several of the colony opacity-associated proteins and leukocyte association proteins were subjected to 125I-peptide mapping of protein bands separated by polyacrylamide electrophoresis in the presence of sodium dodecyl sulfate. The structural similarities and differences among these heat-modifiable surface proteins were studied, as well as their similarities with the major protein of the gonococcal outer membrane. A relatively high apparent degree of structural homology is found among the heat-modifiable proteins from different strains of opaque colony gonococcal forms. There is also some apparent structural homology for 125I-peptides of heat-modifiable versus major proteins of the gonococcal outer membrane.